Pelatihan Manajemen Pemeliharaan Itik Kerinci Menuju Kawasan Sentra Produksi Di Kabupaten Kerinci - noferdiman noferdiman (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
The community service program (CSP) aims to: (1). Increase productivity of Kerinci ducks which are germplasm by utilizing the potential of food crops (rice bran) and plantation waste (palm kernel meal) which can be used as Kerinci duck feed resources with biotricho technology, (2). Increase Kerinci ducks population using breeding center technology with simple selection and hatching machines. The CSP activity was carried out by the method of active interaction between the implementers and the target groups involved in this activity, namely: Keluarga Damai and Maju Jaya Mandiri Farmers Group in Tanjung Harapan Village, Kerinci Regency. Some of the implemented programs are: (1). Conseling and training, including: biotricho technology, breeding center technology, utilizing potential local feed stuffs, duck rations, duck selection, and hatching machines, (2). Practicing directly the application of biotricho technology to make formulation of local feed stuffs and breeding center technology with hatching machine technology and simple selection of Kerinci ducks at the Farmer Group level. The results of the activity indicated that the CSP program can be implemented and responded well by the Farmers Group in Tanjung Harapan Village, Kerinci Regency and the implementation of the CSP program is very beneficial for farmers, and Implementing Institutions because it can be a medium to transfer Knowledge and Technology especially the local Kerinci duck which is not done much yet and is not focused. Therefore, the results of studies and the efforts to develop local Kerinci ducks in the countryside are not optimal.